Wax coating affects postharvest shelf-life of non-cooled sweet pepper - T N Balamohan, V Arumugam (Journal of Spices and Aromatic Crops, 2014)
Investigations were carried out to determine the effect of wax coating on physical and quality parameters in sweet pepper (Capsicum annuum) cv. Indra under ambient storage (25±5 oC). Wax coating with carnauba wax at 2% produced the lowest physiological loss of weight (PLW), and increased shelf-life, total soluble solids (TSS), total sugar content and ascorbic acid. Wax concentration of > 2% coating had little or no effect, on physical and biochemical characters. This suggested that 2% wax coating increased the shelf life, while concentration of > 2% did not enhance its shelf life.